At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To solve the equation [tex]\( \left(\frac{1}{4}\right)^{x+1} = 32 \)[/tex], we can take the following step-by-step approach:
1. Rewrite the equation in terms of exponents:
[tex]\[ \left(\frac{1}{4}\right)^{x+1} = 32 \][/tex]
2. Express the base [tex]\(\frac{1}{4}\)[/tex] as [tex]\((4)^{-1}\)[/tex]:
[tex]\[ \left(4^{-1}\right)^{x+1} = 32 \][/tex]
3. Simplify the left side using the properties of exponents [tex]\((a^m)^n = a^{m \cdot n}\)[/tex]:
[tex]\[ 4^{-(x+1)} = 32 \][/tex]
4. Rewrite 32 as a power of 2 for easier manipulation:
[tex]\[ 32 = 2^5 \][/tex]
5. Express the base 4 in terms of 2:
[tex]\[ 4 = 2^2 \][/tex]
Therefore,
[tex]\[ 4^{-(x+1)} = (2^2)^{-(x+1)} \][/tex]
Which simplifies to:
[tex]\[ 2^{-2(x+1)} = 2^5 \][/tex]
6. Since the bases are the same, set the exponents equal to each other:
[tex]\[ -2(x+1) = 5 \][/tex]
7. Solve for [tex]\(x\)[/tex]:
[tex]\[ -2(x+1) = 5 \][/tex]
[tex]\[ -2x - 2 = 5 \][/tex]
[tex]\[ -2x = 5 + 2 \][/tex]
[tex]\[ -2x = 7 \][/tex]
[tex]\[ x = -\frac{7}{2} \][/tex]
So, the solution to the equation [tex]\( \left(\frac{1}{4}\right)^{x+1} = 32 \)[/tex] is [tex]\( x = -\frac{7}{2} \)[/tex].
The correct answer is B. [tex]\( -\frac{7}{2} \)[/tex].
1. Rewrite the equation in terms of exponents:
[tex]\[ \left(\frac{1}{4}\right)^{x+1} = 32 \][/tex]
2. Express the base [tex]\(\frac{1}{4}\)[/tex] as [tex]\((4)^{-1}\)[/tex]:
[tex]\[ \left(4^{-1}\right)^{x+1} = 32 \][/tex]
3. Simplify the left side using the properties of exponents [tex]\((a^m)^n = a^{m \cdot n}\)[/tex]:
[tex]\[ 4^{-(x+1)} = 32 \][/tex]
4. Rewrite 32 as a power of 2 for easier manipulation:
[tex]\[ 32 = 2^5 \][/tex]
5. Express the base 4 in terms of 2:
[tex]\[ 4 = 2^2 \][/tex]
Therefore,
[tex]\[ 4^{-(x+1)} = (2^2)^{-(x+1)} \][/tex]
Which simplifies to:
[tex]\[ 2^{-2(x+1)} = 2^5 \][/tex]
6. Since the bases are the same, set the exponents equal to each other:
[tex]\[ -2(x+1) = 5 \][/tex]
7. Solve for [tex]\(x\)[/tex]:
[tex]\[ -2(x+1) = 5 \][/tex]
[tex]\[ -2x - 2 = 5 \][/tex]
[tex]\[ -2x = 5 + 2 \][/tex]
[tex]\[ -2x = 7 \][/tex]
[tex]\[ x = -\frac{7}{2} \][/tex]
So, the solution to the equation [tex]\( \left(\frac{1}{4}\right)^{x+1} = 32 \)[/tex] is [tex]\( x = -\frac{7}{2} \)[/tex].
The correct answer is B. [tex]\( -\frac{7}{2} \)[/tex].
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.